2009
DOI: 10.1074/jbc.m109.017046
|View full text |Cite
|
Sign up to set email alerts
|

C Terminus of Hsc70-interacting Protein Promotes Smooth Muscle Cell Proliferation and Survival through Ubiquitin-mediated Degradation of FoxO1

Abstract: Forkhead transcription factors (FoxOs) play a pivotal role in controlling cellular proliferation and survival. The cellular level of these factors is tightly regulated through the phosphoinositide 3-kinase/Akt and ubiquitin-mediated degradation. However, the ubiquitin ligases responsible for the degradation of FoxO1 and the relevance of this regulation to smooth muscle cell (SMC) proliferation and survival have not been fully identified. Here we showed that overexpression of C terminus of Hsc70-interacting pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 43 publications
0
46
0
1
Order By: Relevance
“…In addition to its well-characterized three-tetratricopeptide repeats (TRP) domain that allows it to interact with chaperones such as Hsc70/Hsp70 and Hsp90, it also has charged domain, and U-box domain that confers E3 ubiquitin ligase activity and facilitates the polyubiquitination of chaperone substrates [13]. Studies have shown that CHIP plays important roles in the regulation of pathophysiological processes through promoting the degradation of various target proteins including cystic fibrosis transmembrane conductance regulator (CFTR), ErBB2, Foxo1, myocardin, Ask1, p53, Tau, and ataxin 1 proteins [27,28]. Several studies have demonstrated that the expression of CHIP at mRNA and protein levels is regulated by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its well-characterized three-tetratricopeptide repeats (TRP) domain that allows it to interact with chaperones such as Hsc70/Hsp70 and Hsp90, it also has charged domain, and U-box domain that confers E3 ubiquitin ligase activity and facilitates the polyubiquitination of chaperone substrates [13]. Studies have shown that CHIP plays important roles in the regulation of pathophysiological processes through promoting the degradation of various target proteins including cystic fibrosis transmembrane conductance regulator (CFTR), ErBB2, Foxo1, myocardin, Ask1, p53, Tau, and ataxin 1 proteins [27,28]. Several studies have demonstrated that the expression of CHIP at mRNA and protein levels is regulated by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…C-terminus of Hsc70-interacting protein (CHIP) is highly expressed in the heart and blood vessels, and the C-terminus has a cochaperone/ubiquitin ligase with a dual function. Under the stimulus of TNF-α, CHIP promotes the smooth muscle cells to degrade and ubiquitination (110). Ring finger and WD repeat domain 2 (COP1), a ring-finger E3 ubiquitin ligase regulated by insulin, has a key role in survival of mammalian cells.…”
Section: Ubiquitination Of Foxo Proteinsmentioning
confidence: 99%
“…By virtue of previously described functions in other muscle types, this analysis implicated numerous GR targets as novel candidates to modulate ASM function. For example, FOXO1 had been shown to regulate skeletal muscle atrophy and vascular smooth muscle (VSM) proliferation (34,35), but has not been studied in the lung or in ASM. Likewise, the GR targets, HES1, NR4A3, and MSX1, are transcription factors that have been implicated in smooth muscle biology (36-38), but have not been studied in ASM or asthma.…”
Section: Go Analysis Predicts That Gr Signaling Impacts Many Facets Omentioning
confidence: 99%